ART PHOTOGRAPHY MARKETING SEBAGAI PROMOSI WISATA DI BUMDES PURI MATARAM YOGYAKARTA - Supri Hartanto; Septian Ajie Permana (Muria Jurnal Layanan Masyarakat, 2020)
The purpose of this service is to provide training to tour managers in Bumdes Puri Mataram, Tridadi, Sleman, Yogyakarta and photographers to use the Art of Photography Marketing in tourism promotion. In various references and journals the implementation of this service has never been done. The dedication process is done by combining photographic art techniques conceptualized in a tourist vehicle, edited with photoshop and uploaded on social media for promotional media. This Art Photography Marketing involves various parties from Puri Mataram, 80 Photographers, 4 make up artists, 6 models, and activity committees. Through this Art of Photography Marketing can increase tourism promotion which has an impact on increasing tourist income, as well as increasing the ability of photographers to produce works of photography related to increased tourism. This makes the tourist sites given this program can help more widely for the community and is expected to increase the number of tourist visitors.